Ammonia level and Alzheimer type 2 astrocytes in the brain of deceased patients with liver cirrhosis of the varying degree - Shulyatnikova, T. V.; Tumanskyi, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (Запорізький державний медичний університет, 2023)
The aim of the study – comparative analysis of the ammonia level and Alzheimer type 2 astrocytes in the brain cortex and white matter of cerebral hemispheres, hippocampus, thalamus, striatum and cerebellum in the deceased patients with liver cirrhosis of classes A, B and C according to Child–Pugh. Materials and methods. The study was performed on the brain of deceased 90 patients (65 ± 3 years) suffered from non-alcoholic liver cirrhosis (LC) of classes A (n = 30, group “A”), B (n = 30, group “B”) and C (n = 30, group “C”) according to Child–Pugh score, among which 59 (65.55 %) patients had clinical symptoms of hepatic encephalopathy of I–IV grades. The control group included postmortem brains of 30 patients (59.0 ± 2.5 years) who died from acute cardiovascular insufficiency and did not suffer from liver diseases or intoxication. A retrospective analysis of clinical and laboratory data from case histories was carried out. For histochemical (HC) determination of the ammonia in paraffin sections of the cerebral cortex and white matter, hippocampus, thalamus, striatum and cerebellum we used the protocol with Nessler’s reagent proposed by Gutierrez-de-Juan et al. (2017). In the noted brain regions, the analysis of HC ammonia optical density was performed in five standardized fields of view (×200) of the microscope scope A1 “Carl Zeiss” (Germany) with Jenoptik camera progress Gryphax 60 N-C1ꞌ1.0x426114 (Germany) using ImageJ software; in each noted brain region the number of Alzheimer’s type 2 astrocytes (AA2) was counted per twenty standardized fields of view at magnification ×400. Мета роботи – порівняльний аналіз рівня аміаку й астроцитів Альцгеймера 2 типу в тканині кори та білої речовини великих півкуль головного мозку, гіпокампу, таламусу, смугастого тіла та мозочка у померлих хворих на цироз печінки класу А, В та С за Чайлд–П’ю. Матеріали та методи. Дослідили головний мозок (ГМ) 90 померлих хворих (віком 65 ± 3 роки) на неалкогольний цироз печінки (ЦП) класу А, В і С за Чайлд–П’ю. Визначили 3 групи спостережень: «А» (n = 30), «В» (n = 30) та «С» (n = 30). У 59 (65,55 %) хворих груп «А», «В» і «С» виявили клінічну симптоматику печінкової енцефалопатії I–IV ступенів. У групі контролю дослідили ГМ 30 померлих (віком 59,0 ± 2,5 року) від гострої серцево-судинної недостатності, в яких не діагностували захворювання печінки або інтоксикацію. У кожному випадку виконали ретроспективний аналіз клінічних і лабораторних даних історій хвороб. Методом V. Gutiérrez-de-Juan et al. (2017) з використанням реактиву Несслера здійснили гістохімічне (ГХ) визначення вмісту аміаку в парафінових зрізах тканини кори та білої речовини великих півкуль головного мозку (ВПГМ), гіпокампу, таламусу, смугастого тіла та мозочка. У цих відділах ГМ виконали порівняльний аналіз оптичної щільності ГХ експресії аміаку в п’яти стандартизованих полях зору (при збільшенні ×200) мікроскопа Scope A1 «Carl Zeiss» (Germany) з камерою Jenoptik Progres Gryphax 60N-C1 J; у кожному відділі ГМ у двадцяти стандартизованих полях зору зі збільшенням ×400 обрахували кількість астроцитів Альцгеймера 2 типу (АА2).
Рівень аміаку й астроцитів Альцгеймера 2 типу в головному мозку померлих хворих на цироз печінки різних ступенів тяжкості
Shulyatnikova T. V. - ORCID ID: 0000-0002-0196-9935; Tumanskyi V. O.- ORCID ID: 0000-0001-8267-2350.
Keywords: liver cirrhosis; ammonia; hepatic encephalopathy; histocytochemistry; optical density; Alzheimer type 2 astrocytes; bilirubin; цироз печінки; аміак; печінкова енцефалопатія; гістохімія; оптична щільність; астроцити Альцгеймера 2 типу; білірубін